Empowering Entrepreneurial Competencies and Mindset in Teacher Training - Trasberg, Karmen (Acta Paedagogica Vilnensia, 2024)
The article aims to identify the teacher students’ experiences regarding entrepreneurship education in pre-service training to empower the development of the entrepreneurial mindset of future teachers. Estonia belongs to one of the few countries in Europe where entrepreneurship education is a compulsory topic in pre-service teacher education. To frame entrepreneurial studies for future teachers, the competence model was created. Based on literature relating to entrepreneurial education and teacher’s competence model, qualitative research was conducted. Data was collected from 24 in-depth interviews with the teacher students. Inductive content analysis is used as the method of data analysis. The paper argues that addressing transferable competencies (e.g., creative thinking, teamwork and communication skills, self-management) is crucial for promoting entrepreneurial mindset and engagement of teacher students. When planning the content of entrepreneurial studies, experiential learning, authentic assignments, collaborative and reflective methods are the most potential to have an impact on meaningful learning. Teacher students evaluate these activities as motivationally challenging and essential for developing an entrepreneurial mindset. The results of the study are valuable for designing entrepreneurial studies module and integration of entrepreneurial competence as a cross-curricular theme in pre-service teacher education.
Keywords: pre-service teacher training; teacher competencies; entrepreneurship education; entrepreneurial mindset